A poética do cotidiano em Renato Russo: a letra e a música como resistência e contestação - Ozório, Elisângela Maria (2011)
This dissertation is based on the result of reflexions obtained during the research about poetry manifestation on Brazilian music. Among the diverse poetic movements present in songbooks of our country, the one who is the main poet-singer is Renato Russo. Such selection did not happen in a misunderstanding way, but from readings, that demonstrated that the poetry is an art not prisoner to paper, or writing, but to language form, established in sound and metaphoric meaning of material-word. Therefore, writers and theorists, like Paul Zumthor, Octavio Paz, Paul Valéry and Décio Pignatari, integrated dissertation readings, and guided all the research as well. In Paul Zumthor‟s works, the meeting of oral poetry indicated that rock and roll is a poetic manifestation that recovers the vocalized poetry from primitive man. The view that, the dissertation started with the attempt to understand of the musical gender as a poetic and performative language, that rummages, above all, the resistence, the revolution and the liberation of human being from ethical and moral concepts of (post)modern society. In Brazil, the rock poetry becomes more expressive when it receives poetic lyrics that, linked to abrupt achords from musical style, they (re)create and present the reality of the big urban centers, exploring the two faces of: concrete reality and, hence, repetitive, discouraged, with no major attractions, and the possible reality, challenger, based on Utopian ideals. Thus, this dissertation tried to understand how rock and roll graded in poetic manifestation, and how russiana work, closely tied to music, worked verbal sign, joining poetic word to discordant and decanted melody, that units vocalized poetry with tunelesness and minimalist achords of punk rock, from rock and roll